Decrease in parietal cerebral hemoglobin oxygenation during performance of a verbal fluency task in patients with Alzheimer's disease monitored by means of near-infrared spectroscopy (NIRS) — correlation with simultaneous rCBF-PET measurements - Hock, Christoph; Villringer, Kersten; Müller-Spahn, Franz; Wenzel, Rüdiger; Heekeren, Hauke; Schuh-Hofer, Sigrid; Hofmann, Marc; Minoshima, Satoshi; Schwaiger, Markus; Dirnagl, Ulrich; Villringer, Arno (Brain research, 1997)
We used near-infrared spectroscopy (NIRS) to study non-invasively changes in cerebral hemoglobin oxygenation in the frontal and parietal cortex during performance of a verbal fluency task in patients with Alzheimer's disease (AD). Whereas healthy elderly subjects ( n=19, age 67±10 years) showed increases in concentrations of oxygenated hemoglobin [HbO 2] (mean (arbitrary units)±S.E.M., 1.44±0.59) and total hemoglobin [HbT] (0.92±0.81) over the left superior parietal cortex, patients with AD ( n=19, age 71±10 years) showed significant decreases in [HbO 2] (−3.26±1.30, P<0.01) as well as [HbT] (−4.45±1.57, P<0.01). [HbR] decreased slightly in both groups (−0.62±0.29 and −1.18±0.40, respectively). Using two pairs of NIRS optodes placed on the left superior partietal cortex and on the left prefrontal cortex simultaneous increases in [HbO 2] as well as [HbT] in both cortical regions in the healthy elderly subjects ( n=8, age 60±15) were demonstrated during performance of the task. AD patients ( n=10, age 65±13 years) showed decreases in [HbO 2] and [HbT] in the parietal cortex and, at the same time, increases in [HbO 2] and [HbT] in the frontal cortex. Simultaneous NIRS-[HbT] and PET-rCBF measurements showed a significant correlation both when calculated in a `banana' shaped volume approximated by using cortical thresholds as well as when calculated in a semisphere volume of brain tissue beneath the optodes placed on the head surface (patients with AD, n=10). The correlation was dependent on the assumed penetration depth of the near-infrared light and was best for all three NIRS variables ([HbO 2], [HbR] and [HbT]) when calculated using a semisphere radius of 0.45 cm to 1.35 cm. In conclusion, in Alzheimer's disease a marked reduction of regional cerebral blood flow and cerebral hemoglobin oxygenation may occur during activation of brain function, probably mainly in degenerating brain areas, such as the parietal cortex. ©Elsevier Science B.V. All rights reserved.